Analysis of Marketing Mix Strategy in Increasing Brand Awareness: Case Study at Partukkoan Coffee Shop Balige - Gurning, Rosa Paramitha; Batubara, Sri Karunia; Sipahutar, A. Nadyas Qhuita; Sianipar, Yose Jan Petra (International Journal Administration, Business & Organization, 2025)
The coffee shop industry in Balige is experiencing rapid growth which has triggered intense competition. Partukkoan Coffee Shop stands as a legendary business entity that has survived for three generations with a reputation for hosting national figures, yet it faces challenges regarding brand visibility amidst the onslaught of digitally aggressive modern competitors. This study aims to analyze the effect of the marketing mix strategy consisting of product, price, place, and promotion on the Brand Awareness of Partukkoan Coffee Shop Balige. This research employs mixed methods. Quantitative data were collected through questionnaires distributed to 100 respondents selected using the accidental sampling technique, while qualitative data were obtained through in-depth interviews with business owners to strengthen the strategic context analysis. The hypothesis testing results indicate that simultaneously, the marketing mix makes a significant contribution to brand awareness. However, partially, only the Promotion variable is proven to have a positive and statistically significant effect. In contrast, the variables of Product, Price, and Place did not demonstrate a significant effect. These findings indicate that product quality and competitive pricing are considered standard requirements (point of parity) for legacy businesses, implying that the differentiating factor currently lies in communication intensity. The research concludes that Partukkoan's marketing strategy should shift focus from operational development to digital promotion aggressiveness to bridge the gap between strong brand identity and low visibility.